Functionality evaluation and publication of thematic indicators on web portals of Food and Nutrition Security observatories - Espino Reyes, Rosa Carolina; Rodezno Oliva, Josue Ismael; Centeno Sarmiento, Jorge Antonio; Delcid-Carrasco, Javier Enrique (LACCEI, 2025)
Food and Nutritional Security (FNS) is a strategic pillar for sustainable development and the realization of the human right to adequate food. Around the world, FNS observatories and monitoring platforms have emerged as key tools for tracking the availability, access, consumption, and biological use of food, as well as food safety. However, their digital portals often exhibit critical limitations in functionality, usability, data openness, and frequency of updates. This study aimed to design and validated an evaluation instrument to assess the functionality of FNS observatory web portals using global methodological benchmarks. A quantitative, descriptive, and analytical approach was applied, based on the content analysis of 50 portals worldwide. The proposed instrument includes eight sections aligned with FNS pillars and transversal criteria such as digital accessibility, data update frequency, interactivity, and open data availability. Validation was conducted through expert judgment, and results were systematized using descriptive statistics. The findings underscore the relevance of standardized evaluation tools to strengthen data governance, enhance institutional transparency, and support the continuous improvement of digital food information systems globally.